Hatinggian Eco-Park Hotel Resort (Ecological Architecture) (International Journal of Architecture and Urbanism, 2020)
Tourism is a phenomenon based on health needs, conscious, and class assessment in human society as a result of the development of commerce, industry, trade, and the improvement of transportation equipment. Tourism development has a role in increasing employment, encouraging the distribution of business opportunities, encouraging the distribution of national and regional development, and contributing to the country's foreign exchange earnings resulting from the number of foreign tourists visits. North Sumatra Province is one of the 10 (ten) leading tourism destinations in Indonesia. Tourism objects on the market include natural potential, one of which is the Lake Toba region. The existence of Lake Toba, with its natural beauty, makes the surrounding area a priority object and tourist attraction (ODTW). Tourism activities do not always have a good impact. Irresponsible tourism activities will have a negative impact, especially on the environment. For this reason, tourism development requires an ecological architecture design and educates tourists. The goal of design is to make the Eco-Hotel Resort a marine tourism destination with an ecotourism understanding.